Impacts of Extreme Weather Events on Education Outcomes: A Review of Evidence - Venegas Marin, Sergio; Schwarz, Lara; Sabarwal, Shwetlena (The World Bank Research Observer, 2024)
Extreme weather events are increasingly disrupting schooling. Yet, these are underrepresented in the climate change literature. Of 15 review articles on the economic impacts of climate change published since 2010, only three mention the impacts of climate change on education. We review available literature on the effects of weather extremes on education. We outline key pathways through which these events impact education outcomes, as well as the magnitude of those impacts. Evidence implies a significant and adverse relationship between heat and learning. Studies suggest surpassing a high temperature threshold makes learning difficult and results in learning losses. Across studies, each additional day subject to extreme heat reduces learning. Tropical cyclones, floods, and wildfires precipitate school closures, which halt learning. Evidence suggests that one day of school closures leads to one day of learning lost. Weather extremes also negatively impact education outcomes through health, nutrition, poverty, and fragility, among other distal pathways. We discuss the implications of this evidence for policy, including the need to adapt education systems to climate change. Mitigation and adaptation are both urgently needed as extreme weather events become more frequent and severe in the context of climate change.
Keywords: interesting